Interrogating and predicting ionizing radiation effects on telomeres and chromosomes, and implications for long-term risks for human health - Luxton, Jared James, author; Bailey, Susan M., advisor; DeLuca, Jennifer G., committee member; Argueso, Juan L., committee member; Kato, Takamitsu A., committee member (Colorado State University. Libraries, 2020)
Space remains the final frontier of exploration. NASA plans to send humans back to the lunar surface by 2024, establishing a permanent lunar base thereafter and embarking humanity on a new era of endeavors. As we approach these grand ventures, the long-term impacts of spaceflight on human health, particularly from chronic exposure to space radiation, remain poorly understood in terms of risks for degenerative disease and cancer. Even less is understood about the effects of deep space flight. These collective unknowns present significant challenges to ensuring and safeguarding astronaut performance during and after spaceflight missions.Telomeres are the ends of linear chromosomes; they shorten with each cell division and also in response to stress, but can be elongated via lifestyle choices and environmental factors, thus telomeres provide an integrated view of an individual's health status during, and after, given exposures. We hypothesized that longitudinally monitoring telomeres as well as chromosome rearrangements (genomic instability) in astronauts aboard the International Space Station (ISS) throughout spaceflight missions would provide an informative view of astronaut health and long-term risks incurred from spaceflight. For astronauts during spaceflight aboard the ISS, we observed telomeric and cytogenetic evidence for transient activation of Alternative Lengthening of Telomeres (ALT), concurrent with significant increases in chromosomal rearrangements (inversions) during spaceflight – RNA sequencing of individuals in extreme environments also yielded indications of transient ALT activation in response to high levels of chronic stress. Telomere elongation concurrent with significant levels of DNA damage has implications for cancer risk. Methods for predicting telomeric responses to given exposures such as ionizing radiation would provide material improvements in projecting disease risk. A high performance machine learning framework for accurate predictions of telomere length is provided here. Our work provides novel indications of transient ALT activation in humans during chronic exposure to extreme environments, as well as a framework for accurately predicting how an individual's telomere length will change throughout.
Keywords: cancer biology; NASA; biology; radiobiology; cell and molecular biology